In‐Situ Constructuring of Copper‐Doped Bismuth Catalyst for Highly Efficient CO2 Electrolysis to Formate in Ampere‐Level. Issue 1 (6th November 2022) - Shen, Haidong; Zhao, Yike; Zhang, Ling; He, Yuan; Yang, Shaowei; Wang, Tianshuai; Cao, Yueling; Guo, Ying; Zhang, Qiuyu; Zhang, Hepeng
Abstract: CO2 electrochemical reduction (CO2 RR) can mitigate environmental issues while providing valuable products, yet challenging in activity, selectivity, and stability. Here, a CuS‐Bi2 S3 heterojunction precursor is reported that can in situ reconstruct to Cu‐doped Bismuth (CDB) electrocatalyst during CO2 RR. The CDB exhibits an industrial‐compatible current density of −1.1 A cm −2 and a record‐high formate formation rate of 21.0 mmol h −1 cm −2 at −0.86 V versus the reversible hydrogen electrode toward CO2 RR to formate, dramatically outperforming currently reported catalysts. Importantly, the ultrawide potential region of 1050 mV with high formate Faradaic efficiency of over 90% and superior long‐term stability for more than 100 h at −400 mA cm −2 can also be realized. Experimental and theoretical studies reveal that the remarkable CO2 RR performance of CDB results from the doping effect of Cu which optimizes adsorption of the *OCHO and boosts the structural stability of metallic bismuth catalyst. This study provides valuable inspiration for the design of element‐doping electrocatalysts to enhance catalytic activity and durability. Abstract : A Cu‐doped Bi (CDB) electrocatalyst is developed by the in situ reconstruction of a CuS‐Bi2 S3 heterojunction precursor. Benefiting from the doping effect of Cu, CDB delivers an industrial‐compatible current density of −1132 mA cm −2 and a record formate formation rate of 21.0 mmol h −1 cm −2 for the CO2 electrochemical reduction to formate at −0.86 V versus reversible hydrogen electrode.